The mechanism of the state in the modern theoretical and legal researches - Пильгун, Наталія Василівна; Бурбеза, Владислава Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article presents different theoretical and methodological approaches to the definition of «state mechanism». On their basis was selected some concepts of fundamental understanding the law’s categories. The role and the meaning of the state mechanism was substantiated for the general theory of law. The problem and its relevance. The mechanism of the state is one of the main research subjects of the modern theory of law as the fundamental law science. The concept of the mechanism of the state has considerable methodological potential which is used not only to explain the system of government but also detect and study the general laws of the state. In fact, the mechanism of the state is characterized in legal studies as material and organizational basis for the existence of any state, in spite of its political regime or form of government. The state mechanism is important and essential attribute of any state as its “material substance” and “physical embodiment of state power”. However, pointing out the importance of the scientific study of this concept should be stressed out the reasons and factors led to its relevance for the modern theory of law. The main reason is that any fundamental legal study of the state phenomenon applies to the question of the state mechanism as O. Petrishin noted “practical realization of the state’s tasks involves specially formed mechanism…the state mechanism attributes and reflects its institutional aspect of the state. Thus, the development of modern science of the law foresees further doctrinal development concept of the mechanism of the state. The question about the definition of the state mechanism, its nature, structure, principle of formation and functions is still problematic. It can be explained not only by the subjective factor but also by the objective nature, and the diversity of the institute of the state and state legal effects in different historical period. The aim of the article is an analysis of theoretical and methodological approaches which concern the definition of mechanism of the state and researches its characteristic features. The analysis of studies and publications. A significant contribution in solving this problem have been made by V. Averyanov, S. Husarev, A. Kolodiy, V. Kopeychikov, V. Lazarev, M. Tichomirov, V. Shapoval, Y. Shemshumchenko and other native and foreign scientists. Some questions of theoretical and legal determination were the subject of the analysis such authors as G. Bystryk, O. Rakul, V. Sukhonos, N. Kravchenko, V. Shatilo and others. Conclusions. Unlike functional aspect of studying the state mechanism, we can say this mechanism, we can say that this mechanism embodies the material basis of the existence of any modern state. Thanks this it sells its constitutionally detained goals and objectives. At the same time, the state mechanism is a complex and multi-layered internal structure which objectively reflects the functions and tasks of the state. There several basic theoretical and methodological approaches to the definition of state’s mechanism concept. The main difference between them is how to interpret the structural elements of the mechanism. The most “narrow” interpretation of meaning of the state mechanism is based on its identification with the state apparatus. During the past decades other methodology for analyzing the mechanism of the state, was appeared. It includes different degrees of extension of its content. Today it has the dominant character.